(untitled) (Research, Society and Development, 2020)
The Serra do Mar in Cubatão, São Paulo, is crossed by two highways, Anchieta and Imigrantes, and a railroad, connecting Jundiaí to Santos. In the construction of the Santos-Jundiaí (1867) and Anchieta (1947) railroad led to the invasion of Serra do Mar and, thus, bring, until today, serious problems to biodiversity. The Government of the State of São Paulo and the Municipality of Cubatão developed Serra do Mar socio-environmental recovery project that explains removal of people from the Cota neighborhoods and reforestation of the area. In view of this, the objective of the research was to analyze the application of Knowledge Management and Sustainable Economy on the Serra do Mar socio-environmental recovery project to verify the achievement Project’s goals, and to propose innovative points for the effectiveness of its management. The state of the art of the theme was carried out, and qualitative exploratory research and technical focus group was used with the residents of the quota neighborhoods. The results showed that the goals of the Project are being reached and remains in continuous execution, social is practically resolved and the environment is in the regenerative phase of its vegetation cover. It is concluded that there is a continuous need to monitor the process of socio-environmental recovery of the area, thus avoiding irregular settlements that would compromise the environmental recovery: vegetative, water sources and quality of water captured in the Cubatão river.